HEADLINERS; How Nasty Is That? (The New York times, 1982)
Apparently no one told Air Force Lieut. Gen. Charles Donnelly that the honeymoon with the new Soviet leader, Yuri V. Andropov, isn't over yet. The general raised a few eyebrows and a hackle or two last week when he publicly referred to Mr. Andropov as ''nastier than a snake.'' General Donnelly, the commander of United States forces in Japan, offered that and other disparaging remarks before the Kiwanis Club in Agana, Guam. The Pentagon, carefully choosing the form of chastisement, said he had been ''counselled'' for his comments.